Polypill for atherosclerotic cardiovascular disease prevention in Haiti: Eligibility estimates in a low-income country - Yan, Lily D.; Rouzier, Vanessa; Pierre, Jean Lookens; Dade, Eliezer; Sufra, Rodney; Huffman, Mark D.; Apollon, Alexandra; St Preux, Stephano; Metz, Miranda; Sabwa, Shalom; Morisset, Béatrice; Deschamps, Marie; et al. (Frontiers in Epidemiology, 2022)
Cardiovascular (CVD) polypills, including >2 blood pressure medications, and a statin, are an effective, scalable strategy to close the treatment gap that exists in many low-middle-income countries, including Haiti. We estimated the number of Haitian adults eligible for an atherosclerotic CVD (ASCVD) polypill, and the number of potentially preventable CVD events if polypills were implemented nationally. We used cross-sectional data from the Haiti CVD Cohort, a population-based cohort of 3,005 adults ≥18 years in Port-au-Prince, to compare two polypill implementation strategies: high-risk primary and secondary prevention. Primary prevention included: a) age≥40 years, b) hypertension, or c) predicted 10-year ASCVD risk ≥7.5%. Secondary prevention eligibility included history of stroke or myocardial infarction. We used the 2019 Global Burden of Disease database and published polypill trials to estimate preventable CVD events (nonfatal MI, nonfatal stroke, cardiovascular death) over a 5-year timeline. Among 2,880 participants, the proportion of eligible adults for primary prevention were: 51.6% for age, 32.5% for hypertension, 19.3% for high ASCVD risk, and 5.8% for secondary prevention. Based on current trends, an estimated 462,509 CVD events (95%CI:369,089-578,475) would occur among adults ≥40 years in Haiti from 2019-2024. Compared with no polypill therapy, we found 32% or 148,003 CVD events (95%CI:70,126-248,744) could be prevented by a combined primary and secondary prevention approach in Haiti if polypills were fully implemented over 5 years. These modeling estimates underscore the potential magnitude of preventable CVD events in low-income settings like Haiti. Model calibration using observed CVD events, costs, and implementation assumptions are future directions.